Peningkatan Hasil Belajar Siswa Melalui Model Pembelajaran Cooperative Script - Hamsah, Lina; Talakua, Mozarrt Winston (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2022)
This study aims to determine the improvement of student learning outcomes on the concept of human skeleton through the Cooperative Script learning model. This type of research is Classroom Action Research (PTK) which consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were all grade IV students of SD Negeri Kalibaru, Seram Bagain Barat Regency, totaling 28 students. To obtain data in this study, researchers used instruments in the form of tests and non-tests. The test used in this study is a learning outcome test. The non-test instrument used is an observation sheet. Data obtained from learning outcomes will be processed quantitatively using descriptive statistics. Based on the results of the study, it was concluded that the Cooperative Script learning model can improve the learning outcomes of IV students of Kalibaru State Elementary School, West Seram Regency on the concept of human skeleton. This is indicated by the number of students who completed learning before giving action was 14.29%, after being given action the number increased by 53.57% in cycle I to 67.86%, and again increased by 14.28% in cycle II to 82.14%.